Leading the way : the busy nurse's guide to supervision in long-term care - Pillemer, Karl A.; Rheaume, Christine (Clifton Park, New York : Delmar Cengage Learning, 2013)
This guide has been designed ro help you take on the challenges of being a supervisor and to make the transition from staff nurse to supervisor. It will present some of the challenges and expectations you need to be aware of, and offer advice from others who have been in your shoes.
Introduction: your job as a supervisor -- What is leadership? -- Building an effective team -- Communication: the secret of successful supervision -- Setting an example: teaching and mentoring -- Strategies for staff development -- Documentation -- Managing and organizing for success -- Recognition equals high morale -- Helping staff achieve work/life balance -- Dealing with conflict -- Dealing with your job stress -- Humor at work -- Making diversity work -- Performance management -- Everyday ethics in long-term care.
Includes bibliographical references.
Keywords: LONG-TERM CARE FACILITIES -- ADMINISTRATION